TOILET TRAINING THE PICTURE MEDIA FOR COGNITIVE ABILITY IN GOLDEN AGE PERIOD - lida khalimatus sadiyah (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2017)
Growing and progressing a different event but both of them in the same place. A good growing and progressing will give the result a healthy and quality generations. Toilet training to children is kind of trying for the train in order children can be control do urination and defecate (Hidayat, 2008). In golden age required toilet training, this period almost all of potential of children to be a sensitive period for growing and progress with quick and great. Toilet training to be done for inculcating a good habit to children, especially about self-hygiene. Teaching Toilet Training could be given by many methods, one of them with picture media. Purpose this research analyzes effects of toilet training the picture media for cognitive in golden age period. The research project which used in this research is Quasi-experiment with approach method one group pretest-posttest design. There are two pair groups are 41 responded. Respondent which have good ability before given treatment is 29 respondents (70.7%) and good ability after given treatment is 37 respondents (90,2%) there is an enhancement to cognitive ability, toilet training in golden age period both before and after given treatment. The result of analysis test Wilcoxon signs rank test available the result that has influence Toilet training the picture media for cognitive ability in golden age period at PAUD dan TK Tunas Harapan Bangsa Mojokerto (Ï=0,02). For next researcher, better to increase the cognitive ability in golden age period with picture media can be combined with modeling technique.